Diseases of Rapeseed-mustard and their management - Raj, Kushal; Rathi, Ajit Singh (Indian Farming, 2016)
The rapeseed-mustard crops get affected by a number of diseaseswhich either completely destroys them or affect their quality andproductivity. By disease management of these crops, the farmers are able to salvage them to a large extent.